Electrode film, electrode including same, secondary battery, and method for producing same

By incorporating a heat-treated fluorine-containing binder with lithium metal phosphoric oxide, the electrode film achieves improved mechanical properties, addressing the weakness of existing films and enhancing the manufacturing and performance of secondary batteries.

JP2025512003AActive Publication Date: 2025-04-16LG ENERGY SOLUTION LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024559921
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-20
Filing Date
2023-04-20
Publication Date
2025-04-16
Estimated Expiration
2043-04-20

AI Technical Summary

Technical Problem

Existing electrode films for secondary batteries have weak mechanical properties, leading to defects in subsequent manufacturing processes and affecting the quality of the electrodes.

Method used

The development of an electrode film with improved mechanical properties, achieved by using a fluorine-containing binder, such as polytetrafluoroethylene (PTFE), in combination with a lithium metal phosphoric oxide active material, and heat-treating the binder to enhance fiberization and binding strength.

Benefits of technology

The resulting electrode film exhibits enhanced mechanical properties, including increased elongation at break, improved tensile strength, and better fiberization, which improves the manufacturing processability and performance of secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025512003000001_ABST
    Figure 2025512003000001_ABST
Patent Text Reader

Abstract

The present invention provides an electrode film, comprising an active material and a fluorine-containing binder, the fluorine-containing binder comprising a polytetrafluoroethylene (PTFE) binder, the active material comprising a lithium metal phosphate, the content of the fluorine-containing binder being 0.5 parts by weight to 10 parts by weight based on a total of 100 parts by weight of the electrode film, and having a breaking elongation of 3.5% or more, an electrode, a secondary battery, and an energy storage device each including the electrode film.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode film, an electrode including the same, a secondary battery, and a manufacturing method thereof, and more particularly to an electrode film having improved mechanical properties, an electrode including the same, a secondary battery, and a manufacturing method thereof.

[0002] This application claims priority to Korean Patent Application No. 10-2022-0049211, filed on April 20, 2022, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]

[0003] As the use of fossil fuels increases rapidly, the demand for alternative and clean energy is increasing, and as part of this, the field in which research is most active is the field of power generation and storage using electrochemistry. Currently, a representative example of an electrochemical element that uses such electrochemical energy is a secondary battery, and its range of use is expanding. Lithium secondary batteries, which are representative of such secondary batteries, are not only used as an energy source for mobile devices, but are also being used as a power source for electric vehicles and hybrid electric vehicles that can replace vehicles that use fossil fuels such as gasoline vehicles and diesel vehicles, which are one of the main causes of air pollution, and their range of use is expanding as an auxiliary power source for grid-based power generation.

[0004] The manufacturing process of such a lithium secondary battery can be roughly divided into three steps: an electrode manufacturing process, an electrode assembly manufacturing process, and a chemical formation process, which can be further divided into an electrode mixture mixing process, an electrode coating process, a drying process, a rolling process, a slitting process, a winding process, etc.

[0005] Among these, the electrode mixture mixing process is a process of blending components for forming an electrode active layer where an electrochemical reaction actually occurs in the electrode. In detail, an electrode active material, which is an essential element of an electrode, and other additives such as a conductive material and a filler, a binder for binding between powder particles and adhering to a current collector, and a solvent for imparting viscosity and dispersing powder are mixed to prepare a slurry having fluidity.

[0006] An electrode coating process is performed in which the slurry is applied onto an electrically conductive current collector, and a drying process is performed in which the solvent contained in the electrode mixture slurry is removed. The electrode is then rolled to produce an electrode with a predetermined thickness.

[0007] Meanwhile, the evaporation of the solvent contained in the electrode mixture during the drying process may induce defects such as pinholes and cracks in the formed electrode active layer. In addition, the inside and outside of the active layer may not be dried uniformly, which may cause a powder floating phenomenon due to the difference in the evaporation speed of the solvent, i.e., the powder in the area that is dried first may float up and form a gap with the area that is dried later, thereby degrading the quality of the electrode.

[0008] In order to solve the above problems, a drying device capable of adjusting the evaporation rate of the solvent while drying the inside and outside of the active layer uniformly may be considered. However, such a drying device is very expensive and requires considerable cost and time to operate, which is disadvantageous in terms of manufacturing process.

[0009] Therefore, in recent years, much research has been conducted into the production of dry electrodes that do not use solvents.

[0010] The method for manufacturing a dry electrode includes a process of obtaining a free-standing electrode film by performing a roll calendar process on a mixture of a fiberizable binder (e.g., polytetrafluoroethylene (PTFE)), an active material, and a conductive material. However, if the mechanical strength of the electrode film is weak, it may cause defects in the subsequent electrode manufacturing process. Summary of the Invention [Problem to be solved by the invention]

[0011] The present invention has been made in consideration of the above problems, and has an object to provide an electrode film having improved mechanical properties, an electrode and a secondary battery including the same, and a method for producing the same. [Means for solving the problem]

[0012] In order to achieve the above object, according to one aspect of the present invention, there is provided an electrode having the following embodiment. According to the first embodiment, An active material and a fluorine-containing binder are provided, The fluorine-containing binder includes a polytetrafluoroethylene (PTFE) binder, the active material comprises lithium metal phosphate; The content of the fluorine-containing binder is 0.5 parts by weight to 10 parts by weight based on a total of 100 parts by weight of the electrode film, An electrode film is provided, which is characterized by having a breaking elongation of 3.5% or more.

[0013] According to the second embodiment, in the first embodiment, The lithium metal phosphate may be represented by the following Formula 1. [C1] Life 1-a M a P x M' 1-x O 4 In the above Chemical Formula 1, M is Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, Ti or two or more thereof, and 0≦a≦0.01; M′ is Si, B, N or two or more thereof, and 0≦x≦0.9.

[0014] According to the third embodiment, in the first or second embodiment, The lithium metal phosphate is LiFePO4 may include.

[0015] According to a fourth embodiment, in any one of the first to third embodiments, When the active material is a lithium metal oxide, the electrode film may have a breaking elongation of 3.5% to 6.5%.

[0016] According to the fifth embodiment, in any one of the first to fourth embodiments, The electrode film may include an active material, a fluorine-containing binder, and a conductive material.

[0017] According to the sixth embodiment, in the fifth embodiment, The conductive material may include activated carbon, graphite, carbon black, Ketjen black, carbon nanotubes, or two or more of these.

[0018] According to the seventh embodiment, in the fifth or sixth embodiment, The content of the active material may be 85 to 98 parts by weight, the content of the conductive material may be 0.5 to 5 parts by weight, and the content of the fluorine-containing binder may be 0.5 to 10 parts by weight.

[0019] According to the eighth embodiment, in any one of the first to seventh embodiments, The electrode film may be manufactured by a dry process.

[0020] According to the ninth embodiment, A step of heat treating the fluorine-containing binder at 290°C to 310°C; preparing a mixture comprising an active material and the heat-treated fluorine-containing binder; A step of kneading the mixture at a temperature in the range of 70°C to 200°C and at a pressure equal to or higher than normal pressure to produce a mixture mass; pulverizing the mixture mass to obtain a mixed powder for an electrode; and forming an electrode film by feeding the electrode mixed powder between a plurality of rolls and calendering the powder.

[0021] According to the tenth embodiment, in the ninth embodiment, The step of kneading to prepare a mixture mass may be carried out in a kneader under atmospheric pressure or higher.

[0022] According to the eleventh embodiment, There is provided a method for manufacturing an electrode, comprising laminating the electrode film according to any one of the first to eighth embodiments to a current collector.

[0023] According to the twelfth embodiment, in the eleventh embodiment, In the laminating step, the compression ratio of the electrode film may be 30% to 50%.

[0024] According to the thirteenth embodiment, A current collector; An electrode is provided, comprising the electrode film according to any one of the first to eighth embodiments located on at least one surface of the current collector.

[0025] According to the fourteenth embodiment, in the thirteenth embodiment, The current collector may further include a conductive primer layer on at least one surface.

[0026] According to the fifteenth embodiment, There is provided a secondary battery comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, wherein at least one of the positive electrode and the negative electrode is an electrode according to the thirteenth or fourteenth embodiment.

[0027] According to the 16th embodiment, An energy storage device including the secondary battery according to the fifteenth embodiment as a unit battery is provided. Effect of the Invention

[0028] According to one embodiment of the present invention, a fluorine-containing binder is heat-treated at 290°C to 310°C, and then mixed with an active material to manufacture an electrode film, and in this case, when the fluorine-containing binder is heat-treated in advance, the bonding between primary particles in the secondary particles of the fluorine-containing binder (e.g., PTFE, etc.) is improved due to melt inter-diffusion on the surface between the binder particles, and as a result, the fluorine-containing binder is easily fiberized in the subsequent electrode film manufacturing process. As a result, an electrode film containing a fluorine-containing binder that is more fiberized than conventional electrode films has significantly improved mechanical properties and increased film productivity.

[0029] The following drawings attached to this specification illustrate preferred embodiments of the present invention and, together with the detailed description of the invention, serve to further understand the technical ideas of the present invention. Therefore, the present invention should not be interpreted as being limited only to the matters described in the drawings. [Brief description of the drawings]

[0030] [Figure 1] 1 is a schematic diagram illustrating a process for manufacturing an electrode film according to an embodiment of the present invention. [Diagram 2] 1 is a schematic diagram of an electrode lamination process according to an embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] Hereinafter, a preferred embodiment of the present invention will be described in detail with reference to the attached drawings. Prior to this, the terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as being in accordance with the meaning and concept of the technical idea of ​​the present invention, in accordance with the principle that the inventor himself can appropriately define the concept of the term in order to best describe the invention. Therefore, it should be understood that the embodiment described in this specification and the configuration shown in the drawings are only one most preferred embodiment of the present invention, and do not represent the entire technical idea of ​​the present invention, and therefore there may be various equivalents and modifications that can be substituted for them at the time of this application.

[0032] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. Unless otherwise specified in the context, the singular expression includes the plural expression.

[0033] Throughout the specification, when a part "comprises" a certain element, it does not mean excluding other elements, but means that the part may further include other elements, unless otherwise specified.

[0034] According to one aspect of the invention, An active material and a fluorine-containing binder are provided, The fluorine-containing binder includes a polytetrafluoroethylene (PTFE) binder, the active material comprises lithium metal phosphate; The content of the fluorine-containing binder is 0.5 parts by weight to 10 parts by weight based on a total of 100 parts by weight of the electrode film, An electrode film is provided, which is characterized by having a breaking elongation of 3.5% or more.

[0035] The active material includes lithium metal phosphate.

[0036] The lithium metal phosphate may be represented by the following Chemical Formula 1: [Chemical formula 1] Life 1-a M a P x M' 1-x O 4 In the above Chemical Formula 1, M can be Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, Ti, or two or more thereof, and 0≦a≦0.01; M′ can be Si, B, N, or two or more thereof, and 0≦x≦0.9.

[0037] Specific examples of the lithium metal phosphate include LiFePO 4 etc.

[0038] In this case, doping with M or M' element is advantageous in improving the structural stability of the lithium iron phosphate base material and preventing the structural collapse of the lithium iron phosphate cathode active material after multiple charge-discharge cycles.

[0039] According to an embodiment of the present invention, the electrode film may include an active material, a fluorine-containing binder, and a conductive material.

[0040] The conductive material is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, graphite such as natural graphite and artificial graphite; carbonaceous materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; needle-like or branch-like conductive whiskers such as zinc oxide whiskers, calcium carbonate whiskers, titanium dioxide whiskers, silicon oxide whiskers, silicon carbide whiskers, aluminum borate whiskers, magnesium borate whiskers, potassium titanate whiskers, silicon nitride whiskers, silicon carbide whiskers, and alumina whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, which may be used alone or in mixtures of two or more. Specifically, in order to uniformly mix the conductive material and improve the conductivity, the conductive material may include at least one selected from the group consisting of activated carbon, graphite, carbon black, and carbon nanotubes, and more specifically, may include activated carbon.

[0041] The fluorine-containing binder may be a fluorine-containing polymer, and may specifically include polytetrafluoroethylene (PTFE). The fluorine-containing binder may include polytetrafluoroethylene alone, or may further include one or more of PVdF-based copolymers such as PVdF (polyvinylidene fluoride) and PVdF-HFP (polyvinylidene fluoride-co-hexafluoropropylene).

[0042] In this regard, the breaking elongation of the electrode film refers to the elongation rate at which the electrode film breaks, specifically, refers to the deformation rate at which the electrode film cannot be deformed any further and breaks in the process of increasing a load applied to change the length of the electrode film to a predetermined standard.

[0043] According to an embodiment of the present invention, the breaking elongation of the electrode film may be measured using a UTM (ZwickRoell) device under the following test conditions. Test conditions: ASTM D 638, Pre-load 0.01kg / cm, Test Speed ​​50mm / min

[0044] In addition, in the present specification, the tensile strength of the electrode film means the maximum stress until the electrode film breaks, and specifically, means a value obtained by dividing the maximum tensile load at the point when the electrode film cannot be deformed any further and breaks in the process of increasing a load applied to change the length of the electrode film to a predetermined standard, by the original cross-sectional area of ​​the specimen.

[0045] The elastic modulus is a constant that indicates the ratio of the deformation force (stress) and strain of an elastic body, and is also called the elastic coefficient. When an external force is applied to an object and it is deformed, the deformation force caused by the external force and the strain caused by the deformation are proportional to the range in which the deformation is not too large (Hooke's law), and the proportional constant at this time is called the elastic modulus.

[0046] In this specification, the elastic modulus of the electrode film means a proportional constant of the deformation force to the strain caused by the deformation of the electrode film.

[0047] According to an embodiment of the present invention, the tensile strength and elastic modulus of the electrode film may be measured using a UTM (ZwickRoell) device under the following test conditions. Test conditions: ASTM D 638, Pre-load 0.01kg / cm, Test Speed ​​50mm / min

[0048] The breaking elongation of the electrode film is 3.5% or more, and according to one embodiment of the present invention, the breaking elongation of the electrode film may be 3.5% to 6.5%, or 3.5% to 6.0%, or 3.9% to 5.5%, or 3.9% to 5.0%, or 5.0% to 5.5%.

[0049] The content of the fluorine-containing binder is 0.5 to 10 parts by weight based on a total of 100 parts by weight of the electrode film of the present invention. According to an embodiment of the present invention, the content of the fluorine-containing binder may be 0.5 to 5 parts by weight, or 0.5 to 3 parts by weight, or 3 to 10 parts by weight based on a total of 100 parts by weight of the electrode film.

[0050] If the content of the fluorine-containing binder is less than 0.5 parts by weight, it is impossible to manufacture an electrode film by molding the mixed powder formed by the pulverization process, and if it exceeds 10 parts by weight, there is a problem that the mixed powder becomes more non-uniform and the physical properties of the film are deteriorated, which is not preferable.

[0051] The electrode film may include an active material, a fluorine-containing binder, and a conductive material.

[0052] According to an embodiment of the present invention, the content of the active material may be 85 parts by weight to 98 parts by weight, the content of the conductive material may be 0.5 parts by weight to 5 parts by weight, and the content of the fluorine-containing binder may be 0.5 parts by weight to 10 parts by weight. Also, the content of the active material may be 85 parts by weight to 96 parts by weight, or 90 parts by weight to 98 parts by weight, or 90 parts by weight to 96 parts by weight, or 96 parts by weight to 98 parts by weight, the content of the conductive material may be 0.5 parts by weight to 5 parts by weight, or 0.5 parts by weight to 1 part by weight, or 1 part by weight to 5 parts by weight, and the content of the fluorine-containing binder may be 0.5 parts by weight to 5 parts by weight, or 5 parts by weight to 3 parts by weight, or 3 parts by weight to 10 parts by weight.

[0053] When the contents of the active material, conductive material, and fluorine-containing binder satisfy these ranges, the fluorine-containing binder can be sufficiently fiberized in a subsequent kneading process to form a mixture mass, the mixed powder formed in a pulverizing process can be easily molded to manufacture an electrode film, the physical properties of the electrode film can be ensured, and the content of the active material can be ensured to prevent a problem of capacity reduction and ensure sufficient conductivity.

[0054] On the other hand, in some cases, a filler, which is a component that suppresses the expansion of the electrode, may be further added to the electrode layer, and the filler is not particularly limited as long as it does not induce chemical changes in the battery and is a fibrous material. For example, olefin polymers such as polyethylene and polypropylene, and fibrous materials such as glass fiber and carbon fiber may be used.

[0055] According to one aspect of the invention, A current collector; and an electrode film according to an embodiment of the present invention positioned on at least one surface of the current collector.

[0056] The current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, copper, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used. In addition, the current collector may have fine irregularities on its surface to increase the adhesive strength of the positive electrode active material, and may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0057] Furthermore, the current collector may be entirely or partially coated with a conductive primer layer to reduce the surface resistance and improve adhesion. Here, the conductive primer layer may include a conductive material and a binder. The conductive material is not limited as long as it is a material having conductivity. Examples of the conductive material include carbon-based materials, metal materials (metal powder or metal fiber), conductive whiskers, conductive metal oxides, conductive polymers, etc. Examples of carbon-based materials include natural graphite, artificial graphite, graphene, carbon black, denka black, acetylene black, ketjen black, super P, channel black, furnace black, lamp black, thermal black, carbon nanotubes, graphite nanofibers, and carbon nanofibers. Examples of metal materials include copper, nickel, aluminum, and silver. Examples of conductive whiskers include zinc oxide whiskers, calcium carbonate whiskers, titanium dioxide whiskers, silicon oxide whiskers, silicon carbide whiskers, aluminum borate whiskers, magnesium borate whiskers, potassium titanate whiskers, silicon nitride whiskers, silicon carbide whiskers, and alumina whiskers. Examples of conductive metal oxides include titanium oxide. Examples of conductive polymers include polyphenylene derivatives. These may be used alone or as a mixture of two or more of them.

[0058] The binder may be a fluorine-based binder (including PVDF and PVDF copolymers) or an acrylic binder that dissolves in a solvent, and may include a water-based binder such as styrene butadiene rubber (SBR).

[0059] According to one aspect of the invention, A step of heat treating the fluorine-containing binder at 290°C to 310°C; preparing a mixture comprising an active material and the heat-treated fluorine-containing binder; Kneading the mixture at a temperature in the range of 70°C to 200°C under a pressure equal to or higher than normal pressure to produce a mixture mass; pulverizing the mixture mass to obtain a mixed powder for an electrode; and forming an electrode film by inserting the electrode mixed powder between a plurality of rolls and calendering the powder.

[0060] The method for producing an electrode according to the present invention will now be described in detail. First, the fluorine-containing binder is heat-treated at 290°C to 310°C.

[0061] The fluorine-containing binder is separately heat-treated in advance before being mixed with the active material, whereby primary particles in secondary particles of the fluorine-containing binder (e.g., PTFE, etc.) are firmly bound to each other by melt inter-diffusion on the surface between the binder particles, and as a result, the fluorine-containing binder can be easily fiberized in the subsequent process of manufacturing an electrode film.

[0062] The electrode film containing the fluorine-containing binder, which is more fibrous than conventional electrode films, has significantly improved mechanical properties and can increase the productivity of the film.

[0063] The heat treatment of the fluorine-containing binder may be carried out in an air atmosphere using an apparatus such as a furnace.

[0064] The heat treatment temperature of the fluorine-containing binder is 290°C to 310°C, and according to one embodiment of the present invention, may be 290°C to 300°C, or 300°C to 310°C, or 292°C to 308°C, or 293°C to 307°C.

[0065] If the heat treatment temperature of the fluorine-containing binder is less than 290° C., the heat treatment effect is not obtained, whereas if it exceeds 310° C., sheeting is not possible, which is disadvantageous in terms of film processability.

[0066] Next, a mixture containing an active material and the heat-treated fluorine-containing binder is prepared.

[0067] In this case, the mixing for preparing the mixture is performed so that the active material and the heat-treated fluorine-containing binder are uniformly distributed and mixed in the form of powder, and therefore, the mixing may be performed by various methods that simply allow for mixing of the active material and the heat-treated fluorine-containing binder. However, since the electrode film of the present invention is prepared by a dry preparation method that does not use a dispersion medium, the mixing may be performed by dry mixing, and may be performed by putting the materials into a device such as a blender. According to an embodiment of the present invention, a mixture may be prepared that further includes a conductive material in addition to the active material and the heat-treated fluorine-containing binder.

[0068] In order to ensure uniformity, the mixture may be prepared by mixing in a mixer at 5,000 rpm to 20,000 rpm for 30 seconds to 2 minutes, more specifically, at 10,000 rpm to 15,000 rpm for 30 seconds to 1 minute.

[0069] The fluorine-containing binder is not limited to a specific one as long as it can be made into fine fibers by the step of preparing the mixed powder and contains fluorine as described above. The fine fiberization refers to a process of dividing a polymer into fine particles, and can be performed, for example, by using mechanical shearing force. As a specific example of such a fluorine-containing binder, a fluorine-containing polymer can be used as described above, and specifically, it can include polytetrafluoroethylene (PTFE) alone, or polytetrafluoroethylene and one or more PVdF-based copolymers such as PVdF (polyvinylidene fluoride) and PVdF-HFP (polyvinylidene fluoride-co-hexafluoropropylene) can be further included.

[0070] Next, the mixture is kneaded at a temperature in the range of 70° C. to 200° C. under a pressure equal to or higher than normal pressure to produce a mixture mass.

[0071] In the conventional technology, high shear mixing such as in a jet mill is performed to fiberize the binder, but this mixing causes problems such as the active material being pulverized and the formed fibers being cut. Therefore, in the present invention, the above problems are solved by using a low shear kneading method instead of high shear mixing.

[0072] The kneading method is not limited to a specific method. In a specific embodiment of the present invention, the kneading may be performed by a kneading machine such as a kneader.

[0073] This kneading process is a step in which the fluorine-containing binder is fibrous and binds or connects the powders of the active material and conductive material, thereby forming a mixture mass with a solid content of 100%.

[0074] Specifically, the kneading may be controlled at a speed of 10 rpm to 100 rpm. For example, the kneading may be controlled at a speed of 20 rpm or more or 70 rpm or less within the above range. The kneading may be performed for 1 minute to 30 minutes. For example, the kneading may be performed at a speed of 40 rpm to 70 rpm within the above range for 3 minutes to 10 minutes. Meanwhile, the kneading may be controlled at a shear rate in the range of 10 / s to 500 / s. In one specific embodiment of the present invention, the kneading may be performed for 1 minute to 30 minutes, and the shear rate may be controlled in the range of 30 / s to 100 / s.

[0075] Moreover, the kneading step may be carried out under high temperature and pressure conditions equal to or higher than atmospheric pressure, more particularly, under pressure conditions higher than atmospheric pressure.

[0076] More specifically, the kneading may be carried out by heating the mixture at a temperature in the range of 70°C to 200°C, specifically 90°C to 150°C.

[0077] If the temperature is low and outside the above temperature range, it becomes difficult to form fibers of the fluorine-containing binder and lumps by kneading during kneading, and it becomes difficult to form a film during calendaring. If the temperature is too high, the fluorine-containing binder is rapidly fibrous, and there is a problem that the previously formed fibers may be cut later by excessive shear force, which is undesirable.

[0078] Also, the mixing may be performed under a pressure equal to or higher than atmospheric pressure, specifically, 1 to 100 atmospheres, more specifically, 10 to 80 atmospheres. When the pressure range is satisfied, problems such as cutting of fibers formed due to application of excessive shear force and pressure, or excessively high density of the mixture mass can be prevented. That is, according to the present invention, when a low shear mixing process is performed under high temperature and pressure conditions equal to or higher than atmospheric pressure instead of high shear mixing, the intended effect of the present invention can be achieved.

[0079] Next, the mixture mass is pulverized to obtain a mixed powder for an electrode. Specifically, the mixture lump produced by the kneading may be immediately calendered. However, in this case, the mixture lump needs to be pressed to produce a thin film, which may result in an excessively high density of the film or an inability to obtain a uniform film. Therefore, according to the present invention, the produced mixture lump is subjected to the pulverization step.

[0080] In this case, the pulverization step may be performed using equipment such as, but not limited to, a blender or grinder, and the pulverization step may be performed at a speed of 5,000 rpm to 20,000 rpm for 30 seconds to 10 minutes, more specifically, at a speed of 10,000 rpm to 18,000 rpm for 30 seconds to 2 minutes.

[0081] When the above-mentioned grinding speed and time are satisfied, sufficient grinding can be performed to form powder of a size suitable for filming, and the problem of a large amount of fine powder being generated in the mixture mass can be prevented. If necessary, a classification process can be performed to select powder exceeding or below a certain size.

[0082] Next, the electrode powder mixture is placed between a plurality of rolls and calendared to form an electrode film.

[0083] Referring to FIG. 1, in a process 100 for forming an electrode film, a plurality of rolls 110 are arranged at a distance from each other, and the mixed powder 120 for an electrode obtained in the previous step is placed between adjacent rolls 110. The rolls 110 are rotated in opposite directions to roll and form the mixed powder 120 into a sheet or film through a powder sheeting step, and then a film for an electrode having a final target thickness is obtained by multiple calendering steps.

[0084] Specifically, the calendering may be a step of processing the mixed powder for an electrode into a film shape, for example, to prepare a film shape having an average thickness of 50 μm to 300 μm.

[0085] At this time, the calendering is performed, for example, by rolls that face each other. At this time, the temperature of the rolls is 50° C. to 200° C., and the rotation speed ratio of the rolls can be controlled in the range of 1.0 to 2.0.

[0086] When the calendering step is completed, a dry electrode film that serves as an electrode mixture can be produced. Such a dry electrode film is also known as a free standing film.

[0087] The dry electrode film thus manufactured does not contain a solvent, and therefore has little fluidity and is easy to handle, and can be processed into a desired shape to be used in the manufacture of various electrodes. In addition, when the dry electrode film of the present invention is used in the manufacture of an electrode, the drying process for removing the solvent can be omitted, which not only significantly improves the manufacturing process of the electrode, but also solves problems such as cracking of the active material and cutting of the fibrous fluorine-containing binder that were problems in the manufacture of existing dry electrodes.

[0088] Meanwhile, in the present invention, the dry electrode film has a porosity of 20% to 50%, and preferably, the porosity can be controlled to a value of 40% or less or 30% or less within the above range. When the porosity satisfies such a range, impregnation of the electrolyte is facilitated, improving life characteristics and output characteristics, and since it is not necessary to increase the volume to achieve the same capacity, the energy density per volume is improved. In one embodiment of the present invention, the porosity can be calculated by the following formula using the actual density calculated based on the actual density and composition of each component by measuring the apparent density of the dry electrode film. Porosity (%) = {1-(apparent density / actual density)} x 100

[0089] According to one aspect of the invention, According to an embodiment of the present invention, there is provided a method for manufacturing an electrode, comprising laminating an electrode film onto a current collector.

[0090] The lamination step may be a step of rolling the electrode film obtained by the method for manufacturing an electrode film according to an embodiment of the present invention onto a current collector to a predetermined thickness. The lamination may also be performed using a lamination roll, and the lamination roll may be maintained at a temperature of 25°C to 250°C.

[0091] According to an embodiment of the present invention, the compression ratio of the electrode film may be 30% to 50%, or 35% to 50%, or 40% to 50%.

[0092] The compression ratio of the electrode film is defined as the ratio of the thickness to which the electrode film is compressed at the moment of lamination, and can be expressed by the following formula 1.

[0093] [Formula 1] Compression ratio (%) = T p / T 1 ×100 In formula 1, T p means the pressed thickness of the electrode film at the lamination stage, T 1means the thickness of the electrode film before the lamination step.

[0094] In the present invention, by adjusting the compression ratio in the lamination step to satisfy a specific range, it is possible to provide an appropriate density and porosity of the electrode film and excellent adhesion between the electrode film and the current collector.

[0095] When the compression ratio of the electrode film is in the range of 30% to 50%, the pressure applied to the electrode film is sufficient, the adhesive strength between the electrode film and the current collector is improved, and the electrode film is prevented from peeling off from the current collector after the lamination process. Also, the density of the electrode film is unnecessarily increased to show a low porosity relative to the target porosity, or the current collector is damaged.

[0096] In an embodiment of the present invention, when an electrode film is laminated on both sides of the current collector, the compression ratio (%) of Equation 1 may be expressed as Equation 2 below.

[0097] [Formula 2] 30≦(T 1 +0.5T c -0.5T gap ) / T 1 ×100≦50 In Equation 2, T 1 means the thickness of the electrode film before lamination, and T c means the thickness of the current collector, and T gap means the distance between the first rolling roll and the second rolling roll.

[0098] In addition, the rolling ratio of the electrode film after the lamination step may be 20% or less, or 18% or less, or 15% or less, or in the range of 5% to 15%, or 6% to 15%, or 7% to 15%, or 9% to 13%.

[0099] Here, the rolling ratio is defined as the ratio of the thickness of the electrode film after the lamination step to the thickness of the electrode film before the lamination step, and can be expressed by the following Equation 3.

[0100] [Formula 3] Rolling ratio (%) = (T 1 -T 2 ) / T 1 ×100 In the formula 3, T 1 indicates the thickness of the electrode film before the lamination stage, T 2 indicates the thickness of the electrode film after the lamination step.

[0101] When the rolling ratio satisfies the above range, appropriate density and porosity of the electrode film and adhesive strength between the electrode film and the current collector can be achieved.

[0102] The increase rate of apparent density before and after lamination of the electrode film with the current collector can be expressed by the following formula 4.

[0103] [Formula 4] Apparent density increase rate (%) = (D 2 -D 1 ) / D 1 ×100 D 1 is the apparent density (g / cm) of the electrode film before lamination. 3 ), D 2 is the apparent density (g / cm) of the electrode film after the lamination step. 3 ) is shown.

[0104] The increase rate of the apparent density of the electrode film before and after lamination with the current collector may be 5% to 30%, or 7% to 25%, or 10% to 20%. 1 and D. 2 is 2.75g / cm 3 ~3.5g / cm 3 On the other hand, when the increase rate of the apparent density of the electrode film satisfies the above range, the adhesive strength between the electrode film and the current collector is improved, and problems such as the porosity being out of the target range or damage to the positive electrode active material or current collector can be prevented.

[0105] The apparent density of the electrode film before and after lamination with the current collector can be calculated by measuring the weight and thickness of the electrode film before lamination, measuring the weight and thickness of the electrode after lamination, and determining the weight and thickness of the film excluding the weight and thickness of the current collector.

[0106] The active material loading of the dry electrode film is 3 mAh / cm 2 ~15mAh / cm 2 For details, see 4mAh / cm 2 ~10mAh / cm 2 It could be.

[0107] Here, the loading amount of the active material is a value calculated by the following Equation 5. [Formula 5] Active material loading (mAh / cm 2 ) = Capacity of active material (mAh / g) × Content ratio of active material in dry electrode film (wt%) × Weight per unit area of ​​dry electrode film (g / cm 2 )

[0108] In addition, the interface resistance between the dry electrode film and the current collector is 5 Ω cm 2 For details, see below: 2Ω·cm 2 Here, the interfacial resistance may be calculated by applying a current of 100 μA to the electrode using a multi-probe (MP) resistance measurement method and measuring the resistance between the dry electrode film and the current collector layer as a potential difference measured between multiple probes. If the interfacial resistance range is satisfied, the battery performance of a secondary battery manufactured later can be improved.

[0109] 2 is a schematic diagram of a step of laminating an electrode film on both sides of a current collector according to an embodiment of the present invention. That is, in the laminating step 200, the electrode film 230 obtained in the previous step is rolled to a predetermined thickness and attached to the current collector 220 using a pair of laminating rolls 210, thereby finally obtaining an electrode 240.

[0110] According to another embodiment of the present invention, there is provided a dry electrode manufactured by the method for manufacturing the dry electrode, and a secondary battery including the dry electrode, in which the dry electrode is a positive electrode, and an electrode assembly including the positive electrode, the negative electrode, and a separator is housed in a battery case (cylindrical case, prismatic case, pouch type, etc.) together with a lithium-containing non-aqueous electrolyte, and an energy storage device including the same as a unit battery is provided.

[0111] At this time, the specific structures of the secondary battery and the energy storage device are well known in the art, and therefore, description thereof will be omitted in this specification.

[0112] Meanwhile, according to one embodiment of the present invention, there is provided an apparatus for manufacturing a dry electrode, the apparatus including a blender for mixing a raw material composite including an active material, a conductive material, and a fluorine-containing binder, a kneader for kneading the mixture to prepare a mixture mass, a pulverizer for pulverizing the mixture mass to form a mixed powder for an electrode, a calendar for forming the mixed powder for an electrode into a dry electrode film, and a lamination roll for positioning the dry electrode film on at least one side of a current collector and laminating it.

[0113] The blender is a mixer for mixing raw materials, and as described above, can mix the raw materials for the composite at a speed of 5000 rpm to 20,000 rpm. The kneader is a device for fiberizing the fluorine-containing binder and dispersing the raw materials for the composite in the present invention, and the mixture can be obtained as a mixture mass by kneading with the kneader. In this case, the kneader for obtaining the results according to the present invention can be set to a temperature range of 70°C to 200°C and a pressure condition of normal pressure or higher. More specifically, it can be set to a pressure condition of 90°C to 180°C and a pressure condition of 1 to 100 atmospheres, more specifically, a pressure condition of 10 to 80 atmospheres.

[0114] The pulverizer is a device for pulverizing the mixture mass to form a mixed powder for an electrode, and may be a blender or a grinder.

[0115] The calender is a device for forming the electrode powder mixture into a film shape, and may be, for example, a pair of rollers facing each other, and the thickness of the film can be adjusted by adjusting the distance between them.

[0116] The laminating roll serves to attach the dry electrode film formed by the calendar to at least one surface of a current collector and roll it.

[0117] By using such a calendar and laminating roll, the porosity of the dry electrode film according to the present invention can be determined.

[0118] That is, the dry electrode manufacturing apparatus according to the present invention is characterized by including a kneader and a pulverizer.

[0119] The specific structures of the blender, kneader, calendar, and laminating roll are conventionally known, and detailed explanations thereof will be omitted in this specification.

[0120] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples according to the present invention can be modified in various forms, and the scope of the present invention is not limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.

[0121] Comparative Example 1 <Manufacturing of electrode films> Lithium iron phosphate (LiFePO 4A mixture was prepared by feeding 96 g of polytetrafluoroethylene (LFP), 1 g of carbon black as a conductive material, and 3 g of polytetrafluoroethylene (PTFE) as a fluorine-containing binder into a blender and mixing at 50 rpm for 5 minutes. The temperature of the kneader was maintained at 150° C., and the mixture was fed into the kneader, and then operated at a speed of 50 rpm for 5 minutes under a lid pressure of 1.1 atmospheres to obtain a mixture lump. The mixture lump was fed into a blender, pulverized at 10,000 rpm for 1 minute, and classified using a sieve with 1 mm-sized openings to obtain a mixed powder for an electrode. The prepared mixed powder for an electrode was then fed into a wrap calender (roll diameter: 160 mm, roll temperature: 100° C.) to prepare a film for an electrode. The thickness of the prepared film for an electrode was 80 μm.

[0122] Examples 1 to 3 <Manufacturing of electrode films> An electrode film was prepared in the same manner as in Comparative Example 1, except that polytetrafluoroethylene (PTFE) as a fluorine-containing binder was heat-treated in an air atmosphere at the heat treatment temperature and heat treatment time shown in Table 1 below using a furnace, and then cooled to room temperature of 25°C.

[0123] Comparative Examples 2 and 3 <Manufacturing of electrode films> An electrode film was prepared in the same manner as in Comparative Example 1, except that polytetrafluoroethylene (PTFE) as a fluorine-containing binder was heat-treated in an oven under an air atmosphere at the heat treatment temperature and time shown in Table 1 below, and then cooled to room temperature of 25°C.

[0124] Comparative Example 4 <Manufacturing of electrode films> Lithium iron phosphate (LiFePO 4An electrode film was produced in the same manner as in Comparative Example 1, except that 87 g of polytetrafluoroethylene (LFP), 1 g of carbon black as a conductive material, and 12 g of polytetrafluoroethylene (PTFE) as a fluorine-containing binder were used, and the polytetrafluoroethylene (PTFE) was heat-treated in a furnace under an air atmosphere at the heat treatment temperature and for the heat treatment time shown in Table 1 below, and then cooled to room temperature of 25° C.

[0125] Performance evaluation The electrode films produced in Examples 1 to 3 and Comparative Examples 1 to 4 were subjected to the following evaluations, and the results are shown in Table 1.

[0126] (1) Breaking elongation (%) Measurements were performed using a UTM (ZwickRoell) device under the following test conditions. Test conditions: ASTM D 638, Pre-load 0.01kg / cm, Test Speed ​​50mm / min

[0127] (2) Elastic modulus (MPa) Measurements were performed using a UTM (ZwickRoell) device under the following test conditions. Test conditions: ASTM D 638, Pre-load 0.01kg / cm, Test Speed ​​50mm / min

[0128] (3) Tensile strength (MPa) Measurements were performed using a UTM (ZwickRoell) device under the following test conditions. Test conditions: ASTM D 638, Pre-load 0.01kg / cm, Test Speed ​​50mm / min

[0129] (4) Table 1 below shows the increase rates of physical properties of the Examples relative to the physical properties of the Comparative Examples. The increase rate was calculated by the formula: [(physical properties of the example - physical properties of the comparative example) / (physical properties of the comparative example) x 100 (%)].

[0130] [Table 1]

[0131] Referring to Table 1, it can be seen that the electrode films of Examples 1 to 3, which were prepared by heat-treating the fluorine-containing binder at 290°C to 310°C and then mixing it with an active material, all had significantly improved mechanical properties, including breaking elongation, elastic modulus, and tensile strength, compared to the electrode films of Comparative Examples 1 to 3, which were not heat-treated or did not meet the heat treatment temperature conditions. In addition, the electrode film of Comparative Example 4 had a breaking elongation of 3.5% or more, but the content of the fluorine-containing binder was 12 parts by weight based on a total of 100 parts by weight of the electrode film, which was outside the range of 0.5 parts by weight to 10 parts by weight based on a total of 100 parts by weight of the electrode film, and therefore showed very low tensile strength properties. [Explanation of symbols]

[0132] 110 rolls 120 Mixed powder 210 Laminate roll 220 Current collector 230 Electrode Film 240 electrodes

Claims

1. An electrode film comprising an active material and a fluorine-containing binder, the fluorine-containing binder comprises a polytetrafluoroethylene (PTFE) binder; the active material comprises lithium metal phosphate; The content of the fluorine-containing binder is 0.5 to 10 parts by weight based on a total of 100 parts by weight of the electrode film; An electrode film having a breaking elongation of 3.5% or more.

2. The electrode film according to claim 1 , wherein the lithium metal phosphate is represented by the following Chemical Formula 1: [Chemical formula 1] LiFe 1-a M a P x M’ 1-x O 4 In the formula 1, M is Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, Ti or two or more thereof, and 0≦a≦0.01; M′ is Si, B, N or two or more thereof, and 0≦x≦0.

9.

3. The lithium metal phosphate is LiFePO 4 The electrode film according to claim 1 ,

4. 2. The electrode film according to claim 1, wherein the electrode film has a breaking elongation of 3.5% to 6.5%.

5. The electrode film according to claim 1 , comprising an active material, a fluorine-containing binder, and a conductive material.

6. 6. The electrode film according to claim 5, wherein the conductive material comprises activated carbon, graphite, carbon black, Ketjen black, carbon nanotubes, or two or more of these.

7. 6. The electrode film according to claim 5, wherein the content of the active material is 85 to 98 parts by weight, the content of the conductive material is 0.5 to 5 parts by weight, and the content of the fluorine-containing binder is 0.5 to 10 parts by weight.

8. The electrode film according to claim 1 , wherein the electrode film is produced by a dry process.

9. A method for producing the electrode film according to claim 1, heat treating the fluorine-containing binder at 290°C to 310°C; preparing a mixture comprising an active material and the heat-treated fluorine-containing binder; kneading the mixture at a temperature in the range of 70° C. to 200° C. and at a pressure equal to or higher than atmospheric pressure to produce a mixture mass; pulverizing the mixture mass to obtain a mixed powder for an electrode; and forming an electrode film by feeding the electrode mixed powder between a plurality of rolls and calendering the powder.

10. The method for producing a film for an electrode according to claim 9, wherein the step of kneading to produce a mixture mass is performed in a kneader under a pressure equal to or higher than atmospheric pressure.

11. A method for producing an electrode, comprising laminating the electrode film according to claim 1 to a current collector.

12. The method of claim 11, wherein a compression ratio of the electrode film in the laminating step is 30% to 50%.

13. A current collector; An electrode comprising the electrode film according to claim 1 located on at least one surface of the current collector.

14. 14. The electrode of claim 13, wherein the current collector further comprises a conductive primer layer on at least one surface.

15. A secondary battery comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, wherein at least one of the positive electrode and the negative electrode is the electrode according to claim 13.

16. An energy storage device comprising the secondary battery according to claim 15 as a unit battery.

Citation Information

Patent Citations

  • Electrode for secondary battery

    JP2007026984A

  • Sheet-like active material particle-containing molding for secondary battery electrode, secondary battery electrode, and secondary battery using the same

    JP2016207583A

  • Electrode for energy storage device and method for manufacturing dry electrode film for energy storage device

    JP2019512872A

  • Compositions and methods for dry electrode films with reduced binder content

    JP2021523531A

  • Dry electrode film manufacturing method and manufacturing system

    JP2024508512A